Hubungan Keadilan Organisasi dan Perilaku Kewargaan Organisasi Karyawan Generasi Z Jawa Timur Dengan Mediasi Komitmen - Romadhona, Listina Laily; Prawitowati, Tjahjani (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This research aims to determine the relationship between organizational justice and organizational citizenship behavior by considering the mediating effect of organizational commitment. This research used a quantitative approach and collected data using a questionnaire distributed to generation Z employees in East Java and obtained 118 respondents. Data analysis techniques use descriptive techniques and Partial Least Square Structural Equation (PLS-SEM). The results of the research show that there is a positive and significant relationship between organizational justice and organizational citizenship behavior, there is a positive and significant relationship between organizational justice and organizational commitment, there is a positive and significant relationship between organizational justice and organizational citizenship behavior, and the mediation results of organizational commitment show that there is mediation. partial or partial mediation.